Fully covered metallic stents for anastomotic biliary strictures after living donor liver transplantation. Issue 1 (27th March 2023) - Komatsu, Naohiro; Ozawa, Eisuke; Fukushima, Masanori; Sawase, Hironori; Nagata, Kazuyoshi; Miuma, Satoshi; Miyaaki, Hisamitsu; Soyama, Akihiko; Hidaka, Masaaki; Eguchi, Susumu; Nakao, Kazuhiko
Abstract: Objectives: Anastomotic biliary strictures (ABSs) are common complications following living donor liver transplantation (LDLT). We evaluated the feasibility of a novel removable, intraductal, fully covered, self‐expandable metallic stent (FCSEMS) for the treatment of ABSs following LDLT. Methods: Nine patients with duct‐to‐duct ABSs that developed following LDLT were prospectively enrolled in this study. We placed a short FCSEMS with a long lasso and middle waist formation in each patient's ABS above the papilla and removed it 16 weeks later. Results: The FCSEMS placements were successful in all nine cases. Four patients experienced mild cholangitis, which was resolved with conservative treatment. Additionally, there was one case of distal migration. The FCSEMSs were successfully removed from all the patients, and the clinical success rate was 100%. Stricture recurrence occurred in one (11.1%) patient during the follow‐up period. Limitations: The small number and lack of comparison with other types of FCSEMSs and plastic stents. Conclusions: Intraductal placement of FCSEMSs is useful for treating refractory ABSs after LDLT, although further studies are required with larger sample sizes.